Genetic testing in motor neuron disease and frontotemporal dementia: a 5-year multicentre evaluation. Issue 6 (7th May 2021) - Cairns, Lauren M; Rankin, Julia; Hamad, Asma; Cooper, Nicola; Merrifield, Katrina; Jain, Vani; Rosser, Elisabeth; Rogers, Megan; Buston, Sarah; Stopford, Cheryl; Jones, Gabriela; Lefroy, Henrietta; et al.
Abstract : Introduction: Motor neuron disease (MND) and frontotemporal dementia (FTD) comprise a neurodegenerative disease spectrum. Genetic testing and counselling is complex in MND/FTD owing to incomplete penetrance, variable phenotype and variants of uncertain significance. Affected patients and unaffected relatives are commonly referred to clinical genetics to consider genetic testing. However, no consensus exists regarding how such genetic testing should best be undertaken and on which patients. Objective: We sought to ascertain UK clinical genetics testing practice in MND/FTD referrals, with the aim of helping inform guideline development. Methods: MND/FTD clinical genetics referrals comprising both affected patients and unaffected relatives between 2012 and 2016 were identified and a standardised proforma used to collate data from clinical records. Results: 301 referrals (70 affected, 231 unaffected) were reviewed across 10 genetics centres. Previously identified familial variants were known in 107 cases and 58% subsequently underwent testing (8 of 8 diagnostic and 54 of 99 predictive). The median number of genetic counselling appointments was 2 for diagnostic and 4 for predictive testing. Importantly, application of current UK Genomic Test Directory eligibility criteria would not have resulted in detection of all pathogenic variants observed in this cohort. Conclusion: We propose pragmatic MND/FTD genetic testing guidelines based on appropriate genetic counselling.